Evaluating the conditions for robust mechanism design - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2010)
We assess the strength of the different conditions identified in the literature of robustmechanism design. We focus on three conditions: ex post incentive compatibility,robust monotonicity, and robust measurability. Ex post incentive compatibility hasbeen shown to be necessary for any concept of robust implementation, while robustmonotonicity and robust measurability have been shown to be necessary for robust(full) exact and virtual implementation, respectively. This paper shows that whileviolations of ex post incentive compatibility and robust monotonicity do not easily goaway, we identify a mild condition on environments in which robust measurability issatisfied by all social choice functions over a residual set (i.e., a countable intersectionof open and dense sets) of first-order types. We conclude that, to the extent thatex post incentive compatibility is permissive, robust virtual implementation can besignificantly more permissive than robust exact implementation.